Welfare Costs of Inflation, Seigniorage, and Financial innovation - De Gregorio, Jose. (Washington, D.C. : International Monetary Fund, 1991)
This paper examines the welfare effects of mitigating the costs of inflation. In a simple model where money reduces transaction costs, a fall in the costs of inflation is equivalent to financial innovation. This can be caused by paying interest on deposits, indexing money, or 'dollarizing.' Results indicate that financial innovation raises welfare in low inflation economies while reducing it in high inflation economies, due to the offsetting indirect effect of higher inflation to finance the budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet